Is it Possible to Estimate Adult Ulna and Radius Length? A Radiological Evaluation - Batuhan Gencer; Oğulcan Ünsalan; Hayri Sucu; Tolga Sezer; Alper Şükrü Kendirci; Hakan Eskara (Sakarya Tıp Dergisi)
Objective: Many reasons during childhood may affect the length of the forearm bones, resulting in the need for surgical intervention. Estimating the patient's forearm length during these surgical interventions can aid in surgical planning. The purpose of our study; To evaluate the relationship between the forearm lengths of children and the forearm lengths of their biological parents.Materials and Methods: Forearm anteroposterior radiographs taken in accordance with the standards of young people aged 15-18 years old and their parents aged 30-60 years, who were admitted to our hospital for any reason between 2020-2023 and whose growth was completed, were evaluated.Results: A total of 120 people were included in this study; 40 young people, 80 parents were evaluated. A highly correlated correlation was detected between the radius and ulna lengths of young men and women and the radius-ulna lengths of their mothers (p<0.001 and r>0.7 for each). A moderate correlation was detected between the radius and ulna lengths of young women and the radius-ulna lengths of their fathers (p<0.001 and r>0.5 for each). A very high (strong) relationship was found between the radius length of young men and the radius length of their fathers (p<0.001 and r=0.927) and a high degree of relationship between the ulna length of young men and their fathers' ulna length (p<0.001 and r=0.841). Conclusions: Based on these results, it can be said that the length of the children's forearm bones when they reach adulthood can be predicted by taking into account the forearm bone length of the mother and father. Especially in boys, the forearm length is directly related to the forearm length of their fathers.